Eksistensi Hukum Perdata dalam Mengatur Warisan Terhadap Anak Angkat - Viment Valentino Mendrofa; Debora (J-CEKI : Jurnal Cendekia Ilmiah, 2024)
In Indonesia, the status of adopted children is often a complex issue, because the appointment of children who are legally carried out through court decisions does not automatically get the same rights as biological children, including in terms of inheritance. Although basically the inheritance of adopted children has been regulated in certain regulations including in civil law, this is because regulations on the inheritance rights of adopted children do not clearly provide certainty of their rights. Based on this background, this paper aims to discuss how the legal position of adopted children in relation to the right to inherit the property of adoptive parents according to the Civil Code and how legal protection for adopted children whose inheritance rights are neglected or complicated. The research method used is normative juridical by reviewing and analyzing legislation and literature materials. Staatsblad 129 of 1917 which confirms that adopted children have the same equal position as biological children or biological children so that directly applicable rights legitime portie. Legal protection for adopted children will be directly protected by law after the appointment of children through court decisions.